2007
DOI: 10.1117/12.705033
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale pattern transfer for templates, NEMS, and nano-optics

Abstract: Plasma etching is an enabling technology in nano optic, nanoelectronic devices, nano electro mechanical systems (NEMS) and nanoresolution templates for nano imprint lithography (NIL). With shrinkage, one must overcome significant challenges to meet the stringent profile and CD goals necessary for nanoscale applications. Using the example of Si nanoimprint template fabrication, we show how ion/sidewall/mask interactions can dominate feature profile evolution at the nanoscale and what to look for successful patt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Its most notable merits include a high etching rate (up to 5 mm/min), high selectivity in the photoresist-mask process, and the fact that it can be conducted at room temperature. 11 Moreover, the excellent reproducibility of the process among different silicon wafers shows that it has good process stability.…”
Section: Introductionmentioning
confidence: 99%
“…Its most notable merits include a high etching rate (up to 5 mm/min), high selectivity in the photoresist-mask process, and the fact that it can be conducted at room temperature. 11 Moreover, the excellent reproducibility of the process among different silicon wafers shows that it has good process stability.…”
Section: Introductionmentioning
confidence: 99%
“…As a result of the above described processes, the etching proceeds only in vertical direction (ion bombardment direction) and an anisotropic profile can be achieved. [13,18,[20][21][22][23]. Figure 4 depicts the principle of cryogenic etching.…”
Section: Cryogenic Etchingmentioning
confidence: 99%
“…Thus, fluorine can react spontaneously with silicon on the bottom of the feature, forming volatile SiF4 molecules which desorb from the surface. As a result of these processes, the etching proceeds only in vertical direction (ion bombardment direction) and an anisotropic profile can be achieved 31,[33][34][35][36] . Furthermore Mellaoui et al 37 have demonstrated that after a temperature increase, the previously non-volatile SiOxFy becomes volatile and leads to smooth silicon sidewalls.…”
Section: Rie -Fagmentioning
confidence: 99%